Accessibility of tourism space from a geographical perspective - Zajadacz, Alina (Turyzm/Tourism, 2014)
The accessibility of tourism space is becoming an increasingly significant issue in geographical research due to, amongst other things, demographic changes (an ageing population, growing numbers of people with disabilities) alongside guaranteeing a universal right of access to tourism. The nature of geographical research (physical, socio-economic) allows this issue to be viewed systemically. Drawing on the fields of geography and accessible tourism, this article presents the assumptions of a model which makes a systemic analysis of the factors conditioning the accessibility of tourism space possible. It also highlights the need for further research into the optimal level of detail in universal design principles which can be applied in tourism.